2018
DOI: 10.1371/journal.pone.0195703
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Fe3O4@Au-C225 composite targeted nanoparticles for MRI of human glioma

Abstract: ObjectiveTo study the characterization of Fe3O4@Au-C225 composite targeted MNPs.MethodsFe3O4@Au-C225 was prepared by the absorption method. The immunosorbent assay was used to evaluate its absorption efficiency at C225 Fc. ZETA SIZER3000 laser particle size analyzer, ultraviolet photometer and its characteristics were analyzed by VSM. the targeting effect of Fe3O4@Au-C225 composite targeted MNPs on U251 cells in vitro were detected by 7.0 Tesla Micro-MR; and subcutaneous transplanted human glioma in nude mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Both MRI and pathology supported this conclusion (Figures 11 and 12). Furthermore, MRI in vivo show that the intensity and signal change rate of tumor tissues were decreased after tail vein injection of Fe 3 O 4 @Au-C225 composite targeted MNPs indicated by Ge et al47 Our findings are similar with Ali Shakeri-Zadeh et al48 which states that MNPs could be guided by an external magnetic field and immobilized in the tumor as observed by the dark regions. Recently, some study indicated folate-conjugated gold nanoparticles could increase the efficiency of cancer diagnosis and therapy, which inspires us to improve our modification on Fe 3 O 4 nanoparticles to get better targeting 49…”
Section: Discussionsupporting
confidence: 89%
“…Both MRI and pathology supported this conclusion (Figures 11 and 12). Furthermore, MRI in vivo show that the intensity and signal change rate of tumor tissues were decreased after tail vein injection of Fe 3 O 4 @Au-C225 composite targeted MNPs indicated by Ge et al47 Our findings are similar with Ali Shakeri-Zadeh et al48 which states that MNPs could be guided by an external magnetic field and immobilized in the tumor as observed by the dark regions. Recently, some study indicated folate-conjugated gold nanoparticles could increase the efficiency of cancer diagnosis and therapy, which inspires us to improve our modification on Fe 3 O 4 nanoparticles to get better targeting 49…”
Section: Discussionsupporting
confidence: 89%
“…Particle sizes, polydispersity indexes, and zeta potentials of LPNs were determined 1 hour after preparation by placing the LPNs in a cuvette. 27 A ZETA SIZER3000 laser particle size analyzer and dynamic light scattering software were used to detect their average diameter and surface potential. The tests were conducted in triplicate, and the average data were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting star-shaped nanoparticles were functionalized with polyethyleneimine (PEI) to improve stability and folic acid to induce the targeting ability (Figure 2). Ge Y et al [138] used antibody (McAb) cetuximab (C225) conjugation of Fe 3 O 4 @Au to induce targeting ability for glioblastoma. The functionality of Fe 3 O 4 @Au nano-composites for targeted tumor imaging has been proved in vivo [137][138][139].…”
Section: Metalsmentioning
confidence: 99%